Masculinity in Numafung, a Film Directed by Nabin Subba - Bista, Asmita (SCHOLARS: Journal of Arts & Humanities, 2021)
The prevailing gender practices in the Limbu culture promote asymmetrical power relations not only between males and females but also between dominant males and subordinated males. This practice is portrayed in the feature film Numafung by Nabin Subba. Thus, the paper aims to investigate how the practice of hegemonic masculinity has affected the life of individuals, both males and females in Limbu community in the film. It scrutinizes what sort of problems do the conventional masculine roles bring in the characters’ lives. This paper also intends to assess the reasons that force the males to perform the conventional gender roles. To analyze the text, R.W. Connell’s and Michael Kimmel’s idea of masculinity theory has been used as an approach. These theorists propose that masculinity is a constructed entity that is achieved through constant performance: a series of cues observed, internalized and repeated over time. Illuminating the gender practices in the Limbu culture, Numafung unfolds the cultural dynamics of the Limbu society in the light of hegemonic masculinities. The paper concludes that cultural practices such as ‘sunauli- rupauli,’ ‘mangena’ and ‘jari’ keep their hegemonic masculinity intact. The paper further concludes that the male characters of Numafung embrace hegemonic masculinity because gender is a socio-cultural construction; being part of that society, one hardly can escape from the socially enforced gender roles.